Anastomotic Repair versus Free Graft Urethroplasty for Bulbar Strictures: A Focus on the Impact on Sexual Function - Matthias Beysens; Enzo Palminteri; Willem Oosterlinck; Anne-Françoise Spinoit; Piet Hoebeke; Philippe François; Karel Decaestecker; Nicolaas Lumen (Advances in Urology)
Objectives. To evaluate alterations in sexual function and genital sensitivity after anastomotic repair (AR) and free graft urethroplasty (FGU) for bulbar urethral strictures. Methods. Patients treated with AR (n=31) or FGU (n=16) were prospectively evaluated before, 6 weeks and 6 months after urethroplasty. Evaluation included International Prostate Symptom Score (IPSS), 5-Item International Index of Erectile Function (IIEF-5), Ejaculation/Orgasm Score (EOS), and 3 questions on genital sensitivity. Results. At 6 weeks, there was a significant decline of IIEF-5 for AR (−4.8; p=0.005), whereas there was no significant change for FGU (+0.9; p=0.115). After 6 months, differences with baseline were not significant overall and among subgroups. At 6 weeks, there was a significant decline in EOS for AR (−1.4; p=0.022). In the FGU group there was no significant change (+0.6; p=0.12). Overall and among subgroups, EOS normalized at 6 months. After 6 weeks and 6 months, respectively, 62.2 and 52% of patients reported alterations in penile sensitivity with no significant differences among subgroups. Conclusions. AR is associated with a transient decline in erectile and ejaculatory function. This was not observed with FGU. Bulbar AR and FGU are likely to alter genital sensitivity.